Korupsi Di Sektor Publik : Tinjauan Literatur Sistematis Dan Analisis Bibliometrik - Ilmi Farikhoh; Anis Chariri (Integritas: Jurnal Antikorupsi, 2022)
This study aims to systematically analyze and map main research streams, research development, and further research direction in corruption studies. It uses bibliometric analysis to analyze 759 articles in the  Scopus database from 2011 to 2020 through the software VOSviewer version 1.6.17. It concludes that public sector corruption is a topic of interest internationally. Articles by Chan et al. (2011), Williams and Shahid (2016), and articles in the Journal of Financial Crime are the main reference sources. Certain keywords, such as management, regulation, tax evasion, health care, and investment provide a potential focus for research in the future.